Polyclonal Broadly Neutralizing Antibody Activity Characterized by CD4 Binding Site and V3-Glycan Antibodies in a Subset of HIV-1 Virus Controllers - Nyanhete, Tinashe E.; Edwards, Robert J.; LaBranche, Celia C.; Mansouri, Katayoun; Eaton, Amanda; Dennison, S. Moses; Saunders, Kevin O.; Goodman, Derrick; Janowska, Katarzyna; Spreng, Rachel L.; Zhang, Lu; Mudrak, Sarah V.; et al. (Frontiers in Immunology, 2021)
Broadly neutralizing antibodies (bNAbs), known to mediate immune control of HIV-1 infection, only develop in a small subset of HIV-1 infected individuals. Despite being traditionally associated with patients with high viral loads, bNAbs have also been observed in therapy naïve HIV-1+ patients naturally controlling virus replication (Virus Controllers (VCs)). Thus, dissecting the bNAb response in VCs will provide key information about what constitutes an effective humoral response to natural HIV-1 infection. In this study, we identified a polyclonal bNAb response to natural HIV-1 infection targeting CD4 binding site (CD4bs), V3-glycan, gp120-gp41 interface and membrane-proximal external region (MPER) epitopes on the HIV-1 envelope (Env). The polyclonal antiviral antibody (Ab) response also included antibody-dependent cellular phagocytosis of clade AE, B and C viruses, consistent with both the Fv and Fc domain contributing to function. Sequence analysis of envs from one of the VCs revealed features consistent with potential immune pressure and virus escape from V3-glycan targeting bNAbs. Epitope mapping of the polyclonal bNAb response in VCs with bNAb activity highlighted the presence of gp120-gp41 interface and CD4bs antibody classes with similar binding profiles to known potent bNAbs. Thus, these findings reveal the induction of a broad and polyfunctional humoral response in VCs in response to natural HIV-1 infection.